National Prosecutors Survey, 2005 ([Verlag nicht ermittelbar], 2007)
The National Survey of Prosecutors is a biennial survey of chief prosecutors in state court systems. A chief prosecutor is an official, usually locally elected and typically with the title of district attorney or county attorney, who is in charge of a prosecutorial district made up of one or more counties, and who conducts or supervises the prosecution of felony cases in a state court system. Prosecutors in courts of limited jurisdiction, such as municipal prosecutors, were not included in the survey. The survey's purpose was to obtain detailed descriptive information on prosecutors' offices, as well as information on their policies and practices. The data collection instrument was based on questions that were included in the NATIONAL PROSECUTORS SURVEY, 1994 (ICPSR 6785), and added queries on topics of current concern. Variables cover staffing, workload, funding, what type of computer access the office had, whether the office was part of an integrated computerized system with other specific criminal agencies, the use of DNA evidence in plea negotiations of felony trials, which laboratories performed these DNA analyses, juvenile matters, and risks associated with the role of the prosecutor, such as threatening letters or calls, face-to-face assaults, or batter/assaults. The unit of analysis is the district office.